Anosognosia in mild Alzheimer's disease is correlated with not only neural dysfunction but also compensation. Issue 2 (6th February 2018) - Tagai, Kenji; Shinagawa, Shunichiro; Kada, Hidehiro; Inamura, Keisuke; Nagata, Tomoyuki; Nakayama, Kazuhiko
Abstract : Background: Anosognosia in Alzheimer's disease (AD) is a complicated, non‐unitary phenomenon. In a clinical setting, patients with mild AD often preserve their awareness partially. We hypothesized that compensation, as well as neural dysfunction, could be correlated with anosognosia in mild AD. Methods: The severity of anosognosia was evaluated using the Anosognosia Questionnaire for Dementia in 37 subjects with mild AD or mild cognitive impairment due to AD. The subjects also underwent single‐photon emission computed tomography with N‐isopropyl‐p‐[ 123 I]iodoamphetamine. Correlation between the severity of anosognosia and perfusion was assessed, and anosognosia (+) and (−) groups were compared. Results: The severity of anosognosia was relatively mild; the mean Anosognosia Questionnaire for Dementia score was 6.76 ± 14.16. Subjects were divided into two groups: anosognosia (+) ( n  = 11) and anosognosia (−) ( n  = 26). In the single‐photon emission computed tomography data analysis, the severity of anosognosia was correlated with both lower regional cerebral blood flows of the right prefrontal cortex and higher regional cerebral blood flows of the parietal cortex, especially the left temporo‐parietal junction. Conclusions: Our results suggest that anosognosia in mild AD could be correlated with compensation as well as neural dysfunction. We speculate that this compensation may be related to the retrieval of outdated autobiographical memory.